Development of Virtual Reality-Based Learning Media for Islamic Cultural History in Madrasah Ibtidaiyah - Habibullah, Muhammad Romadlon; Rofi'ah, Firda Zakiyatur; Nihayah, Hamidatun (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2026)
The subject of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) plays a crucial role in fostering students’ understanding and appreciation of Islamic civilization. However, its implementation at the Madrasah Ibtidaiyah (MI) level often faces challenges, including limited visual learning resources and a lack of contextualized materials. This study aims to develop a Virtual Reality (VR)-based learning medium to provide an immersive and engaging experience, particularly in exploring the historical legacy of Islam in the Indonesian archipelago. This research employed the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The results of expert validation indicate that the developed media is highly feasible, with scores of 86% from subject-matter experts and 81% from media experts. Field testing further shows a practicality level of 87%, demonstrating that the media is user-friendly and suitable for classroom use. Moreover, the effectiveness of the VR-based media is reflected in the significant improvement of students’ learning outcomes in the experimental group compared to the control group. Overall, VR-based learning media enhances students’ understanding and offers an innovative, technology-integrated, and contextually relevant approach to teaching SKI, with potential for broader application in Islamic education.